Use of learning strategies and their effects on English language learning of Thai adult learners - Kasma Suwanarak, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research aims to explore what a repertoire of learning strategies of Thai EFL students are, how they transfer those strategies to English learning, and to what degree the strategies are beneficial for their English learning achievement. The effects of strategy instruction on the students’ awareness of the language learning strategies are highlighted. Differences of strategy types and frequency of strategy use in different groups of low and high strategy users as well as high and low achievers of English language learning are identified. The study employs a mixed-methods research methodology. The quantitative data are collected through a 40-item general learning strategies questionnaire. The participants are 219 undergraduate students enrolling for a foundation English course. The qualitative data are derived from 32 student participants voluntarily taking part in semistructured interviews. The quantitative findings show that there is no significant difference on the strategies used for general learning and English learning. The students transfer their repertoire of learning strategies as a primary learning tool to contend with their English learning. There is positive correlation between the learning strategy use and the English learning achievement. The strategy instruction does not show a significant increase in strategy use. High and low achieving students use similar learning strategies; nevertheless, the frequency of learning strategy use and by what means they use the strategy signifies different types of language learners. The qualitative findings are complemented and help extend the quantitative data. Implications of the study concerning pedagogy in particular suggest a new perspective for the EFL Thai teachers in implementing suitable learning strategies for the students to learn more successfully.